2018
DOI: 10.1029/2018gc007434
|View full text |Cite
|
Sign up to set email alerts
|

Roughness Characteristics of Oceanic Seafloor Prior to Subduction in Relation to the Seismogenic Potential of Subduction Zones

Abstract: We have developed a new approach to characterize the seafloor roughness seaward of the trenches, as a proxy for estimating the roughness of the subduction interface. We consider that abrupt elevation changes over given wavelengths play a larger role in the seismogenic behavior of the subduction interface than the amplitude of bathymetric variations alone. The new database, SubRough, provides roughness parameters at selected spatial wavelengths. Here we mainly discuss the spatial distribution of short‐ (12–20 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 110 publications
(223 reference statements)
2
69
0
Order By: Relevance
“…Individual figures for all subduction zones in Table 2 can be found in Figures S2 to S16 in the supporting information. As can be seen in Figure 7, all the subduction zones with RLR > 50% face mainly smooth to moderately rough seafloor, as shown in Figure 5 and demonstrated as well by Lallemand et al (2018). Figure 8 shows density distributions for the long-wavelength roughness signal of the subduction zones displayed in Figures 6 and 7, illustrating which roughness amplitudes are the most common for these regions.…”
Section: Rupture Areas: Specific Regionsmentioning
confidence: 78%
See 1 more Smart Citation
“…Individual figures for all subduction zones in Table 2 can be found in Figures S2 to S16 in the supporting information. As can be seen in Figure 7, all the subduction zones with RLR > 50% face mainly smooth to moderately rough seafloor, as shown in Figure 5 and demonstrated as well by Lallemand et al (2018). Figure 8 shows density distributions for the long-wavelength roughness signal of the subduction zones displayed in Figures 6 and 7, illustrating which roughness amplitudes are the most common for these regions.…”
Section: Rupture Areas: Specific Regionsmentioning
confidence: 78%
“…Finally, we discuss our main findings by looking at how they relate to the results and concepts previously published. the trench, presented by Lallemand et al (2018). They have developed an approach to estimate the roughness signal at different spatial wavelengths to characterize the seafloor bathymetry prior to subduction, to be used as a proxy for the roughness of the subduction interface (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Global studies have shown that large earthquakes (M W ≥ 7.5) preferably occur along a smooth subduction interface and that rough subducting seafloor is associated with lower seismic coupling and a creep-like behavior (Bassett & Watts, 2015;Lallemand et al, 2018;van Rijsingen et al, 2018;Wang & Bilek, 2014). Global studies have shown that large earthquakes (M W ≥ 7.5) preferably occur along a smooth subduction interface and that rough subducting seafloor is associated with lower seismic coupling and a creep-like behavior (Bassett & Watts, 2015;Lallemand et al, 2018;van Rijsingen et al, 2018;Wang & Bilek, 2014).…”
Section: Comparison With Natural Observationsmentioning
confidence: 99%
“…A number of studies have suggested that subducting basement relief strongly affects megathrust stress state and slip behavior (Das & Watts, 2009; Lallemand et al, 2018; van Rijsingen et al, 2018; Wang & Bilek, 2011, 2014), the rupture dynamics of subduction earthquakes (Kodaira et al, 2000; Lay, 2015; Nakatani et al, 2015; Ye et al, 2016, 2018), and long‐term margin evolution and mass transport as governed by subduction erosion and accretion (Bassett & Watts, 2015; Kopp, 2013; von Huene et al, 2004; von Huene & Scholl, 1991). The overall conceptual picture is one of a structurally disrupted upper plate, a highly heterogeneous stress state, pervasive shearing and fracturing promoted by the irregular geometry, and spatially complex patterns of basal erosion and material underplating.…”
Section: Discussionmentioning
confidence: 99%
“…Also, sediment thickness on the incoming plate differs drastically among subduction zones, ranging from less than 1 km for almost 50% of subduction zones globally, to over 7 km for sediment‐rich subduction zones such as Makran and the Southern Antilles (Scholl et al, 2015). Geomorphological observations indicate spatially variable roughness of subducting seafloor at different subduction margins (Kopp, 2013; Lallemand et al, 2018; Ryan et al, 2009). Field and laboratory observations have also documented variations in other parameters, including plate convergence rate (DeMets et al, 2010), slab dip angle (Hayes et al, 2018), and subduction décollement strength (Ikari, 2019; Ikari & Kopf, 2017).…”
Section: Methodsmentioning
confidence: 99%